Red quarter moon : a search for family in the shadow of Stalin - Konrad, Anne (Tsarist and Soviet Mennonite studies., 2012)
"Anne Konrad's Red Quarter Moon is the gripping account of her search for family members lost and disappeared within the Soviet Union. Konrad's ancestors, Mennonites, had settled the Ukrainian steppes in the late 1790s. An ethno-religious minority, they became special objects of Soviet persecution. Though her parents fled in 1929, many relatives remained in the USSR.